Blue/red light-triggered reversible color switching based on CeO2−x nanodots for constructing rewritable smart fabrics. Issue 18 (5th May 2020) - Ahmed, Sharjeel; Macharia, Daniel K.; Zhu, Bo; Ren, Xiaoling; Yu, Nuo; Chen, Liyun; Chen, Zhigang
Abstract : Rewritable smart fabrics are constructed by coating with CeO2− x /dye/hydroxyethyl cellulose-based inks, and figures can be rapidly and remotely printed by blue-light pen and then erased by red light with the presence of O2 . Abstract : Photoreversible color switching systems (PCSSs) have attracted increasing attention in various applications, but in most PCSSs the discoloration process usually relies on harmful UV light as a stimulus and the recoloration requires high temperature. To solve these problems, we have designed and prepared CeO2− x nanodots as novel photocatalytic components in PCSSs that respond to two kinds of visible light. CeO2− x nanodots are prepared by a solvothermal reaction with l -ascorbic acid as the reducing agent. CeO2− x nanodots with a size of ∼2 nm have a high concentration of oxygen vacancies, which confers a broadened photoabsorption with an edge at 500 nm, as well as a weak photoabsorption tail in the visible region (500–800 nm). To realize the color switching, both the CeO2− x /Dye/H2 O solution and CeO2− x /dye/hydroxyethyl cellulose (HEC)-coated fabrics have been prepared. Under blue (450 nm) light irradiation, both the solution and fabric show a rapid discoloration in 30 s and 150 s, respectively, due to the efficient photocatalytic reduction of the redox dye by CeO2− x . Conversely, red (630 nm) light irradiation with air confers a rapid recoloration in 35 s for the solution and 200 s for the fabric, resulting from CeO2− x -mediated self-catalyzed oxidation. In particular, the required images and letters can be remotely printed on CeO2− x /Dye/HEC-coated T-shirts with a 450 nm laser pen, and then erased with 630 nm light, with high reversibility and stability. Therefore, the present CeO2− x /Dye/HEC PCSSs have great potential to construct rewritable smart fabrics for various applications.